Developing Environmental Awareness and Its Relationship with the Variables of Industrial Product Design - Gumar, Alaa Ismael (Journal of Tikrit University for Humanities, 2020)
The research focused on the (development of environmental awareness and its relationship to the variables of industrial product design) focus on the development of products to be able to meet human needs through the impact of modern technology on product design systems, and its effectiveness in achieving the formal design and functional variables that have an effective effect in creating interaction between the user and products. The study included the question: What is the possibility of achieving environmental awareness to adapt to variables between the user and industrial products? The aim of the research was to shed light on the concepts of environmental awareness and its relationship with modern technology and industrial design variables. The limitations of this study included LG's electronic electrical products manufactured in 2017-2018. The study included the findings and conclusions reached by the researcher. 1- The apparent morphological variables expressed by the mechanism of symbols and signals are realized by the underlying functional system with the appropriateness of use, which is based on several stylistic and technical data, to show the sample models with a relative balance in environmental suitability and formal clarity with the user. 2 - The diversity in the use of modern technologies, which take into account the adoption of the mechanism of multi-functional achieve remarkable harmony in the formal system, and meet the requirements of need, and the ability to give the user the appropriate environmental means to carry out different activities and achieve different objectives in order to achieve environmental awareness.